Pseudidiomarina piscicola sp. nov., isolated from cultured European seabass, Dicenthrarchus labrax - M. Carmen Macián; Teresa Lucena; David R. Arahal; María A. Ruvira; Rosa Aznar; María J. Pujalte (Archives of Microbiology, 2021)
Strain CECT 9734 T , a Gram-negative, aerobic, chemoorganotrophic bacterium, motile by polar flagella, was isolated from cultured European seabass, Dicenthrarchus labrax, in Spain. It grows from 5 to 42 ºC, 6–9 pH and 1–12% total salinity. Major cellular fatty acids are C 15:0 iso, summed feature 9 (C 17:1 iso w9c /C 16:0 10-methyl) and C 17:0 iso. The genome size is 2.5 Mbp and G + C content is 49.5 mol%. Comparative analysis of the 16S rRNA gene sequence shows that the strain is a member of Pseudidiomarina , with highest similarities with Pseudidiomarina halophila (97.0%) and Pseudidiomarina salinarum (96.9%). Phylogenomic tree based on UBCG program shows P. halophila as its closest relative. ANI and in-silico DDH with other Pseudidiomarina spp. are lower than 87 and 20%, respectively, suggesting that strain CECT 9734 T represents a new species, for which we propose the name Pseudidiomarina piscicola sp. nov. and CECT 9734 T (= LUBLD50 7a T = LMG 31044 T ) as type strain.